How to deal with uncertainties regarding the occupational exposure to antineoplastic mixtures: additive effect should always be considered? - Ladeira, Carina (2016)
Risk assessment considerations - The concept that “safe levels of exposure” for humans can be identified for individual chemicals is central to the risk assessment of compounds with known toxicological profiles. Selection of agents for combination chemotherapy regimens involves minimize overlapping of mechanisms of action, antitumor activity and toxicity profile. Although the toxicological profile and mechanism of action of each individual drug is well characterized, the toxicological interactions between drugs are likely, but poorly established at occupational exposure context. The synergistic nature of interactions may help in understanding the adverse health effects observed in healthcare workers, where exposure situations are characterized by complex mixtures of chemical agents, and the levels of individual exposing agents are often not sufficiently high to explain the health complaints. However, if a substance is a genotoxic carcinogen, this would be the “lead effect”; normally, no OEL based on a NOEL would be derived and the level would be set so low that it would be unlikely that other effects would be expected. Aim of the study - Recently research project developed in Portuguese Hospitals characterize the occupational exposure to antineoplastic agents and the health effects related. The project aimed to assess exposure of the different risk groups that handle antineoplastic agents in the hospital setting, namely during preparation and administration of these drugs. Here it is presented and discussed the results in a study developed in two hospitals from Lisbon.